Polska i jej regiony na tle europejskiej przestrzeni społeczno-ekonomicznej - Wojarska, Magdalena; Czeszejko-Sochacka, Małgorzata (Poland and its Regions on the Background of European Socio-Economie Space, 2007)
The main aim of the considerations taken in this article is estimating the level of economic development of Poland and its regions (NUTS 2), as well as the characteristic of socio-economic situation of our country (in the period 1999-2002) on the background of processes taking place in 24 states-members of the European Union. There are employed two methods of data analysis in the research. First one was measure of economic development made by Z. Hellwig. The second method was procedure of vector's elimination created by S. Chomątowski and A. Sokołowski. The analysis showed that the level of economic development of our state was one of the lowest among 25 European Union members.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 206-216